Humanin: Functional Interfaces with IGF-I. (August 2016) - Xiao, J.; Kim, S.-J.; Cohen, P.; Yen, K.
Abstract: Humanin is the first newly discovered peptide encoded in the mitochondrial genome in over three decades. It is the first member of a novel class of mitochondrial derived peptides. This small, 24 amino acid peptide was initially discovered to have neuroprotective effects and subsequent experiments have shown that it is beneficial in a diverse number of disease models including stroke, cardiovascular disease, and cancer. Over a decade ago, our lab found that humanin bound IGFBP-3 and more recent studies have found it to decrease circulating IGF-I levels. In turn, IGF-I also seems to regulate humanin levels and in this review, we cover the known interaction between humanin and IGF-I. Although the exact mechanism for how humanin and IGF-I regulate each other still needs to be elucidated, it is clear that humanin is a new player in IGF-I signaling. Highlights: Humanin is a new player in the regulation of the GH-IGF axis. IGFBP-3 interacts with humanin to influence both IGF-I and humanin bioavailability. Humanin is the first member of a novel class of peptides encoded within small open reading frames in the mitochondrial genome. Humanin has also been shown to have neuroprotective and cytoprotective effects. Humanin decreases circulating IGF-I levels in mouse studies, having a diet-restriction-mimetic effect.